2006
DOI: 10.7202/013973ar
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Fusarium species causing head blight in barley

Abstract: AbstractThe pathogenicity of eightFusariumspecies causing fusarium head blight (FHB) in barley was studied under controlled conditions. Six barley genotypes varying in resistance to FHB were artificially inoculated with six isolates each ofF. acuminatum,F. avenaceum,F. crookwellense,F. culmorum,F. equiseti, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
6
40
4
1
Order By: Relevance
“…in barley in nonepidemical years for FHB in Ontario. Both species are weak FHB pathogens of barley (Xue et al 2006a) and produce low or non-detectable levels of DON (Desjardins 2006). However, these species as a group are important producers of other mycotoxins, including beauvericin, fusarochromanone, moniliformin, zearalenone, T-2, HT-2, and T-2 tetraol, which are more toxic than DON (Desjardins 2006;Hestbjerg et al 2002;Salas et al 1999;Thrane et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in barley in nonepidemical years for FHB in Ontario. Both species are weak FHB pathogens of barley (Xue et al 2006a) and produce low or non-detectable levels of DON (Desjardins 2006). However, these species as a group are important producers of other mycotoxins, including beauvericin, fusarochromanone, moniliformin, zearalenone, T-2, HT-2, and T-2 tetraol, which are more toxic than DON (Desjardins 2006;Hestbjerg et al 2002;Salas et al 1999;Thrane et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…have been proven to be pathogenic on barley and play a role in the etiology of FHB in barley. Xue et al (2006a) were weakly pathogenic in causing FHB in barley. In Europe, F. graminearum, F. culmorum or, more rarely, F. avenaceum are the prevalent species found on barley depending on the country, with F. culmorum being more abundant in northern countries (Bottalico and Perrone 2002;Nielsen et al 2011).…”
mentioning
confidence: 99%
“…These isolates were recovered from wheat, and selected based on their pathogenicity on barley and wheat (Xue et al 2004(Xue et al , 2006 and had been used previously for inoculation in the FHB nursery in Ottawa to screen oat lines for resistance to FHB (Yan et al 2010). Four Fusarium spp.…”
Section: Pathogen Species and Inoculum Productionmentioning
confidence: 99%
“…Among these species, F. graminearum is the principal causal agent of FHB in Canada (Clear et al 1996(Clear et al , 2000Tekauz et al 2008Tekauz et al , 2011. Studies on the pathogenicity of these Fusarium species to wheat and barley revealed that only F. graminearum and F. culmorum were highly pathogenic, and the other species were intermediate or weakly pathogenic (Wong et al 1995;Stack et al 1997;Xue et al 2004Xue et al , 2006. There has been no study on the comparative pathogenicity of Fusarium species causing head blight on oat.…”
mentioning
confidence: 99%
“…The barley in each pan was subsequently inoculated with one of three FG isolates (99E3, 00S-130 or 00S-131; A. Tekauz, Cereals Research Centre, Winnipeg, MB). For inoculation, each isolate was established using the method of Xue et al (2006). Cultures were incubated for 7 d at 22Á258C, under mixed UV and fluorescent lighting on a 12-h light/dark cycle.…”
mentioning
confidence: 99%